The Monetary Authority of Singapore : its establishment, growth and changing role - Maysami, Ramin Cooper (2013)
The Monetary Authority of Singapore (MAS) was established in 1971 to perform essentially all the functions of a central bank except currency issuance that remained under the jurisdiction of the Board of Commissioners of Currency.